Change Management In Islam Perspective - Hujjatullah Fazlurahman (University of Islam Malang, 2018)
This paper attempts to review the literature on the Islamic values and change management, then presents the importance of its delineated dimensions. Two main theories of Islamic perspective and practices are discussed comprehensively based on the Qur’an verses as the ultimate source in Islamic thinking. The review includes the comparison between certain components’ implementations. This reveals that each of dimensions are clearly change management. It suggests that Islamic emphasizes on commercial activities which denied the authors’ opinions on its’ teaching for not governing the materials aspect or success in change management. The Islamic religion seeks to deliver the goodness to all mankind according to its rules and principles. The integrated system of the Islamic worldview encompasses all aspects of both worldly and hereafter- including the aspect of change management. Researcher shows that change management in Islam perspective consist of human, development and change.